Perception of the career adviser about the importance that the educational community attributes to their functions - Jacobo Cano de Escoriaza; Narciso García Nieto (Universidad de La Rioja, 2013)
This paper analyzes the perceptions of school counsellors working in Secondary Schools in the region of Aragon. It studies the assessment of the counsellors' work by the school community. and the different importance given to their tasks as counsellors. It is important to develop strategies to promote collaborative working to improve the quality of the education. The different tasks assigned to school counsellors are so assorted and complex that they have to be carefully analyzed and assessed, because each one has its significance and outreach. We run the risk of mixing the urgent ones with the important ones. To know the perceptions on these tasks by the school community -teachers, parents, tutors, and students- can be very enlightening to make any needed changes.